Regulation of human cerebral cortical development by EXOC7 and EXOC8, components of the exocyst complex, and roles in neural progenitor cell proliferation and survival. - Coulter, Michael E; Musaev, Damir; DeGennaro, Ellen M; Zhang, Xiaochang; Henke, Katrin; James, Kiely N; Smith, Richard S; Hill, R Sean; Partlow, Jennifer N; Kamumbu, A Stacy; Hatem, Nicole; Barkovich, A James; et al. (Genet Med, 2020)
PURPOSE: The exocyst complex is a conserved protein complex that mediates fusion of intracellular vesicles to the plasma membrane and is implicated in processes including cell polarity, cell migration, ciliogenesis, cytokinesis, autophagy, and fusion of secretory vesicles. The essential role of these genes in human genetic disorders, however, is unknown. METHODS: We performed homozygosity mapping and exome sequencing of consanguineous families with recessively inherited brain development disorders. We modeled an EXOC7 splice variant in vitro and examined EXOC7 messenger RNA (mRNA) expression in developing mouse and human cortex. We modeled exoc7 loss-of-function in a zebrafish knockout. RESULTS: We report variants in exocyst complex members, EXOC7 and EXOC8, in a novel disorder of cerebral cortex development. In EXOC7, we identified four independent partial loss-of-function (LOF) variants in a recessively inherited disorder characterized by brain atrophy, seizures, and developmental delay, and in severe cases, microcephaly and infantile death. In EXOC8, we found a homozygous truncating variant in a family with a similar clinical disorder. We modeled exoc7 deficiency in zebrafish and found the absence of exoc7 causes microcephaly. CONCLUSION: Our results highlight the essential role of the exocyst pathway in normal cortical development and how its perturbation causes complex brain disorders.
Keywords: Animals; Brain Diseases; Cell Proliferation; Homozygote; Humans; Mice; Microcephaly; Zebrafish

Biallelic mutations in valyl-tRNA synthetase gene VARS are associated with a progressive neurodevelopmental epileptic encephalopathy. - Friedman, Jennifer; Smith, Desiree E; Issa, Mahmoud Y; Stanley, Valentina; Wang, Rengang; Mendes, Marisa I; Wright, Meredith S; Wigby, Kristen; Hildreth, Amber; Crawford, John R; Koehler, Alanna E; Chowdhury, Shimul; et al. (Nat Commun, 2019)
Aminoacyl-tRNA synthetases (ARSs) function to transfer amino acids to cognate tRNA molecules, which are required for protein translation. To date, biallelic mutations in 31 ARS genes are known to cause recessive, early-onset severe multi-organ diseases. VARS encodes the only known valine cytoplasmic-localized aminoacyl-tRNA synthetase. Here, we report seven patients from five unrelated families with five different biallelic missense variants in VARS. Subjects present with a range of global developmental delay, epileptic encephalopathy and primary or progressive microcephaly. Longitudinal assessment demonstrates progressive cortical atrophy and white matter volume loss. Variants map to the VARS tRNA binding domain and adjacent to the anticodon domain, and disrupt highly conserved residues. Patient primary cells show intact VARS protein but reduced enzymatic activity, suggesting partial loss of function. The implication of VARS in pediatric neurodegeneration broadens the spectrum of human diseases due to mutations in tRNA synthetase genes.
Keywords: Alleles; Anticodon; Child; Child, Preschool; Disease Progression; Epilepsy; Female; Genetic Predisposition to Disease; Humans; Longitudinal Studies; Loss of Function Mutation; Male; Microcephaly; Models, Molecular; Mutation; Neurodevelopmental Disorders; Pedigree; Protein Biosynthesis; Protein Interaction Domains and Motifs; RNA, Transfer; Valine-tRNA Ligase; Whole Exome Sequencing; Whole Genome Sequencing

Loss of the sphingolipid desaturase DEGS1 causes hypomyelinating leukodystrophy. - Pant, Devesh C; Dorboz, Imen; Schluter, Agatha; Fourcade, Stéphane; Launay, Nathalie; Joya, Javier; Aguilera-Albesa, Sergio; Yoldi, Maria Eugenia; Casasnovas, Carlos; Willis, Mary J; Ruiz, Montserrat; Ville, Dorothée; et al. (J Clin Invest, 2019)
Sphingolipid imbalance is the culprit in a variety of neurological diseases, some affecting the myelin sheath. We have used whole-exome sequencing in patients with undetermined leukoencephalopathies to uncover the endoplasmic reticulum lipid desaturase DEGS1 as the causative gene in 19 patients from 13 unrelated families. Shared features among the cases include severe motor arrest, early nystagmus, dystonia, spasticity, and profound failure to thrive. MRI showed hypomyelination, thinning of the corpus callosum, and progressive thalamic and cerebellar atrophy, suggesting a critical role of DEGS1 in myelin development and maintenance. This enzyme converts dihydroceramide (DhCer) into ceramide (Cer) in the final step of the de novo biosynthesis pathway. We detected a marked increase of the substrate DhCer and DhCer/Cer ratios in patients' fibroblasts and muscle. Further, we used a knockdown approach for disease modeling in Danio rerio, followed by a preclinical test with the first-line treatment for multiple sclerosis, fingolimod (FTY720, Gilenya). The enzymatic inhibition of Cer synthase by fingolimod, 1 step prior to DEGS1 in the pathway, reduced the critical DhCer/Cer imbalance and the severe locomotor disability, increasing the number of myelinating oligodendrocytes in a zebrafish model. These proof-of-concept results pave the way to clinical translation.

Biallelic variants in KIF14 cause intellectual disability with microcephaly. - Makrythanasis, Periklis; Maroofian, Reza; Stray-Pedersen, Asbjørg; Musaev, Damir; Zaki, Maha S; Mahmoud, Iman G; Selim, Laila; Elbadawy, Amera; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Gambin, Tomasz; Sorte, Hanne S; et al. (Eur J Hum Genet, 2018)
Kinesin proteins are critical for various cellular functions such as intracellular transport and cell division, and many members of the family have been linked to monogenic disorders and cancer. We report eight individuals with intellectual disability and microcephaly from four unrelated families with parental consanguinity. In the affected individuals of each family, homozygosity for likely pathogenic variants in KIF14 were detected; two loss-of-function (p.Asn83Ilefs*3 and p.Ser1478fs), and two missense substitutions (p.Ser841Phe and p.Gly459Arg). KIF14 is a mitotic motor protein that is required for spindle localization of the mitotic citron rho-interacting kinase, CIT, also mutated in microcephaly. Our results demonstrate the involvement of KIF14 in development and reveal a wide phenotypic variability ranging from fetal lethality to moderate developmental delay and microcephaly.
Keywords: Child; Child, Preschool; Female; Humans; Intellectual Disability; Kinesin; Loss of Function Mutation; Microcephaly; Mutation, Missense; Oncogene Proteins; Pedigree; Phenotype; Protein Domains; Syndrome

Mutations in LNPK, Encoding the Endoplasmic Reticulum Junction Stabilizer Lunapark, Cause a Recessive Neurodevelopmental Syndrome. - Breuss, Martin W; Nguyen, An; Song, Qiong; Nguyen, Thai; Stanley, Valentina; James, Kiely N; Musaev, Damir; Chai, Guoliang; Wirth, Sara A; Anzenberg, Paula; George, Renee D; Johansen, Anide; et al. (Am J Hum Genet, 2018)
The dynamic shape of the endoplasmic reticulum (ER) is a reflection of its wide variety of critical cell biological functions. Consequently, perturbation of ER-shaping proteins can cause a range of human phenotypes. Here, we describe three affected children (from two consanguineous families) who carry homozygous loss-of-function mutations in LNPK (previously known as KIAA1715); this gene encodes lunapark, which is proposed to serve as a curvature-stabilizing protein within tubular three-way junctions of the ER. All individuals presented with severe psychomotor delay, intellectual disability, hypotonia, epilepsy, and corpus callosum hypoplasia, and two of three showed mild cerebellar hypoplasia and atrophy. Consistent with a proposed role in neurodevelopmental disease, LNPK was expressed during brain development in humans and mice and was present in neurite-like processes in differentiating human neural progenitor cells. Affected cells showed the absence of full-length lunapark, aberrant ER structures, and increased luminal mass density. Together, our results implicate the ER junction stabilizer lunapark in establishing the corpus callosum.